Combined pancreas and liver therapies: Resection and ablation in hepato‐pancreatico‐biliary malignancies. Issue 7 (17th January 2013) - Edwards, Jacob; Scoggins, Charles; McMasters, Kelly; Martin, Robert
Abstract Background Combined pancreatic and liver resection for hepato‐pancreatico‐biliary disease is generally considered contraindicated since it is thought to provide little if any survival benefit with high risk of morbidity. Our goal was to review our experience with combined pancreatic and liver resections to better define characteristics that increase risk for perioperative complications after combined resections. Methods A review of prospectively collected IRB approved hepato‐pancreatico‐biliary database was performed from October 2002 to April 2012. Results Twenty‐one cases were identified including all histologies. Perioperative outcomes were examined and the overall mean length of stay was 12.1 days (range: 6–26 days) and no perioperative mortalities (<90 days) were observed. With respect to morbidity 43% of patients experienced any grade of complication, 29% were Grade 3 with no Grade 4 or 5 complications noted. We found a statistically indicated association between BMI > 25 and risk of Grade 3 complications (P = 0.149). The median survival following operation was 11 months (range: 3–148 months). Conclusion Combined pancreas and liver resection for metastatic disease should only be considered in highly selected patients. Tumor histology as well as BMI > 25 (overweight and obese patients) should be considered in the decision making process in an effort to minimize surgical morbidity while potentially improving survival. J. Surg. Oncol. 2013;107:709–712. © 2013 Wiley Periodicals, Inc.